What Motivates Men to Choose Nursing as a Profession? A Systematic Review of Qualitative Studies - KEOGH, BRIAN; YI, MYUNGKEUN (My University, 2016)
Aim This systematic review was conducted to provide a deeper understanding of male nurses’ motivations for choosing nursing as a career. Knowledge of the factors that motivate men to choose nursing will assist in the development of evidence based recruitment strategies to increase the number of men entering the nursing profession. Background Nursing continues to be a female dominated profession. While the number of men entering the profession has improved over the last number of years, they remain low. As demand for healthcare increases internationally, attracting more men into the nursing profession to address nursing shortages and to increase workforce diversification is important. Methods A systematic literature review of qualitative data was conducted. The following electronic databases were searched; CINAHL, Pubmed, PsychINFO, Pubmesh, and Embase from January 1970 to December 2013 in English only. In addition, a search for relevant literature through reference lists and by contacting experts for grey literature was also completed. Inclusion criteria: Qualitative studies which described male nurses’ motivations for choosing nursing were selected. Quality assessment Brunton et al’s (2011) ten item checklist from the Evidence for Policy and Practice Information (EPPI) Centre framework for critiquing qualitative studies was used to assess the quality of the studies. Data collection and analysis: Relevant data was extracted from the included papers and compiled in a data extraction form drawn up by the reviewers. This was checked for accuracy by a second reviewer. The extracted data was coded and then synthesised under four main themes. Results Four main themes were identified which described male nurses motivations for choosing nursing; ‘Early exposure to nursing and other health care professionals’, ‘Choosing nursing as a profession by chance’, ‘Choosing nursing because of extrinsic motivating factors’, and ‘Choosing nursing because of intrinsic motivating factors’. Conclusion To help encourage more men to enter and remain in nursing, recruitment and retention strategies need to focus on addressing the gender stereotypes associated with the nursing profession. In addition, strategies to make nursing more welcoming to men to address attrition rates need to conceptualised, implemented and evaluated.
IN_PRESS
Keywords: Nursing, male nurses, men in nursing, careers in nursing, career choice, choosing nursing, motivation, decision making